Medium-term clinical and imaging outcomes of SilverFlow covered bridging stent implantation using in situ fenestration for aortic arch lesions: a single-centre retrospective cohort study - Xiangyang Shu; Daping Zhang; Pengfei Zhou; Zongjiang Yang; Zhaoxiong Deng; Guangning Liu (Frontiers in Cardiovascular Medicine, 2026)
Introduction Evidence regarding the medium-term performance of SilverFlow covered bridging stents for in-situ fenestrated aortic arch repair remains limited. This study evaluated the clinical and imaging outcomes of SilverFlow covered bridging-stent implantation for the treatment of aortic arch lesions. Methods This single-centre, single-arm retrospective cohort study included consecutive adult patients who underwent in-situ fenestrated aortic arch repair with SilverFlow covered bridging stents between January 2023 and April 2025. The primary outcome was technical success. Secondary outcomes included 30-day major adverse events, mortality, target-vessel patency, aortic remodelling, and reintervention rates. Results Eighty-one patients received 140 SilverFlow covered bridging stents. Technical success was achieved in 70 patients (86.4%). Successful stent deployment, completion of planned fenestrations, and immediate target-vessel patency were each achieved in 98.8% of cases. No intraoperative, in-hospital, or 30-day deaths occurred. The 30-day major adverse-event rate was 25.9%. At 12 months, all 107 assessed branch vessels remained patent. At the latest imaging follow-up, per-vessel and patient-level patency rates were 98.5% and 97.5%, respectively. Significant reductions were observed in maximum aortic diameter (−4.0 mm, P = 0.020), false-lumen diameter (−6.8 mm, P < 0.001), and aneurysm-sac diameter (−8.5 mm, P = 0.010). Complete false-lumen thrombosis increased from 32.5% to 55.0% (P = 0.020). During a median follow-up of 19.0 months, four patients died and seven required aortic- or branch-related reintervention. Freedom from reintervention was 92.4% at 12 months and 90.8% at 24 months. Discussion In this single-centre cohort, in-situ fenestrated aortic arch repair using SilverFlow covered bridging stents demonstrated high immediate reconstruction success, durable target-vessel patency among assessed vessels, and favourable imaging indicators of aortic remodelling during medium-term follow-up. These findings support the feasibility of this technique; however, comparative studies are required to determine its relative effectiveness. Continued imaging surveillance remains essential because reinterventions and device- or aorta-related abnormalities occurred during follow-up.